Clinical heterogeneity in the same generation of siblings with GCK/MODY 2. Issue 1 (January 2015) - Maltoni, Giulio; Zucchini, Stefano; Martini, Anna Lisa; Marasco, Elena; Mantovani, Vilma; Pession, Andrea
Highlights This report is an example of the rare association between type 1 diabetes and monogenic diabetes. It is unusual that the same mutation in glucokinase gene can lead to such different clinical manifestations and therapeutic options. This report broadens the spectrum of the different forms and clinical manifestations of childhood diabetes.